Metal-organic frameworks for advanced aqueous ion batteries and supercapacitors. Issue 6 (November 2022) - Kong, Lingjun; Cheng, Mingren; Huang, Hui; Pang, Jiandong; Liu, Sheng; Xu, Yunhua; Bu, Xian-He
Highlights: The chemical stability and pyrolytic process of MOFs are discussed to guide the applications for aqueous energy storage devices. The latest progress in MOFs and MOF derivatives for aqueous ion batteries and supercapacitors is systematically summarized. The current challenges and opportunities for MOFs and MOF derivatives for aqueous ion batteries and supercapacitors are presented. Abstract: Metal-organic frameworks (MOFs) show great promise for electrochemical energy storage applications due to their high surface area, tunable porosity, ordered crystal structure, and facile tolerability. However, some MOFs with high electrochemical performance are usually unstable in aqueous solutions, which limits their development in aqueous electrochemical energy storage systems, which are cheaper, safer, and more ionically conductive than those operating in conventional organic electrolytes. Numerous efforts have been made to construct stable MOFs or control MOF derivation processes induced by chemical or thermal forces to optimize their properties and performance. Therefore, a review summarizing the MOFs applied in aqueous electrochemical energy storage devices would be useful. In this review, the chemical stability and thermal stability of MOFs under aqueous conditions are discussed. The evolution processes of MOFs when they exceed their stability are summarized. Furthermore, the recent fast-growing literature on MOF-based aqueous ion batteries and supercapacitors is comprehensively reviewed, and guidelines for designing high-performance aqueous electrochemical devices are provided. The current challenges and opportunities for applying MOFs in aqueous electrochemical energy-storage devices are provided. We hope this review will promote the development of MOFs in aqueous electrochemical devices by exploiting the advantages and remedying the disadvantages of MOFs.